Biocatalytic oxidative kinetic resolution of (±)-4-(chlorophenyl)phenylmethanol by Nocardia corallina B-276 - Ramírez, Mario A.; Pérez, Herminia I.; Manjarrez, Norberto; Solís, Aida; Luna, Héctor; Cassani, Julia (Electronic Journal of Biotechnology, 2008)
Chiral diarylmethanols are versatile building blocks for the preparation of biologically active substances, but they are difficult to obtain in enantiopure form. We used Nocardia corallina B-276 for the oxidative kinetic resolution of (±)-4-(chlorophenyl)phenylmethanol, 1. Two experimental methods were used: 1) Suspension of cells in a phosphate buffer solution and 2) Cells in the culture media, in a 3-L bioreactor. After 36 hrs using the first method, the ketone/alcohol ratio was 56/44 and the unoxidized alcohol had an enantiomeric ratio of 93/7, predominating the R-alcohol.